The Role of Islamic Religious Education Teachers in Development Religious Moderation Values in Junior High Schools - Nadiah, Sofi; Mukhtar, Nurkamelia; Aslamiah, Soibatul; Zulmi, Fadhli; Wahyuni, Sri (Al-kayyis: Journal of Islamic Education, 2024)
Religious moderation is the process of understanding and practicing religious teachings fairly and rationally. Religious moderation teaches how to view religious life in a good and correct way, not extreme and radical. Religious moderation also tells us as Muslim to be tolerant among fellow religious believers, not discriminate between races, ethnicities, or religions, and teaches us how to think dynamically and innovatively. This research aims to analyze the role of Islamic religious education teachers in fostering the values ​​of religious moderation from the value aspect of tasamuh, musawah velue, and tahadhur velue in junior high school. This research uses a qualitative method with a case study approach. Data sources were taken from 17 informants through in-depth interviews who were selected using techniques purposive sampling. The data analysis technique is carried out by systematically organizing and understanding all the data obtained with Miles Huberman. Research findings show that the role of Islamic Religious Education teachers in fostering the values ​​of religious moderation is seen from the value aspect tasamuh, musawah value, and tahadhur value in junior high school, the teacher acts as a demonstrator, the teacher as a class manager, the teacher as a mediator and the teacher as an evaluator. In addition, the results of this research can be used as a reference for schools or teachers in developing students in religious moderation.